Neem (Azadirachta Indica) and silk fibroin associated hydrogel: Boon for wound healing treatment regimen - Arfa Nasrine; Soumya Narayana; Mohammed Gulzar Ahmed; Rokeya Sultana; Nadira Noushida; Thriveni Raunak Salian; Mansour Almuqbil; Moneer E. Almadani; Ahmed Alshehri; Adel Alghamdi; Sultan Alshehri; Syed Mohammed Basheeruddin Asdaq (Elsevier, 2023)
Background & Objectives: Wound healing is the complex physiological process of replacing damaged cells or tissue layers. The neem (Azadirachta Indica) has a variety of biological activities, which may hasten the rate at which the wound healing mechanism occurs. Silk fibroin is a biomaterial that is reported for its tissue regeneration activity. So, the present study was designed to assess the effectiveness of a hydrogel comprising neem and silk fibroin biomaterials for the treatment of wounds. Methods: Topical neem hydrogels (N-HG) with and without silk fibroin (N-SFB-HG) were prepared using neem extract, silk fibroin, and guar gum, which act by entrapping the components by forming a gel. Evaluation tests such as Fourier transform infrared spectroscopy (FT-IR), visual emergence, pH, rheological behavior, spreading capacity, drug content, skin irritation, anti-microbial action, in vivo wound healing activity, and stability were carried out. Results: The FT-IR results showed no chemical interaction between the constituents. The formed hydrogels had pH values of 5.87 ± 0.3 for N-HG and 5.76 ± 0.2 for N-SFB-HG. The preferred topical gel viscosity was observed in the N-HG (54.2 ± 3.2cPs) and N-SFB-HG (59.9 ± 4.8cPs) formulations. The formulated hydrogels were sterile and did not irritate the skin. The in vivo wound healing investigation results reveal that the N-SF-HG treatment speeds up the regeneration of the injured area faster when compared to control and N-HG treated groups. Interpretation & Conclusion: These results support the efficacy of the topical hydrogel formulation, including neem and silk fibroin. Therefore, the neem-silk fibroin hydrogel formulation is a therapeutically viable choice that, following necessary clinical research, might be utilized in novel formulations for managing chronic wounds.